High‐ and low‐dose allergen challenges in asthmatic patients using inhaled corticosteroids. (March 2015) - Lee, Wha‐Yong; Southworth, Thomas; Booth, Steven; Singh, Dave; Waller, Derek
<x xml:space="preserve">Abstract</x> Aims The inhaled allergen challenge model has been used previously to investigate the effects of novel anti‐inflammatory drugs in inhaled corticosteroid (ICS)‐naïve asthmatics. The aim of this study was to characterize high‐ and low‐dose allergen challenges in asthmatic patients using ICS. Methods Twenty‐eight asthmatic patients taking ICS (beclomethasone equivalent <1000 μg day−1) were recruited for high‐dose allergen challenge, of whom 10 subsequently also had a repeat low‐dose challenge comprising seven allergen challenges. Induced sputum was collected for measurements of cell counts and supernatant biomarkers. Results The high‐dose allergen challenge caused an early and late asthmatic response in 19 of 28 patients; the mean maximal fall in the forced expiratory volume in 1 s (FEV1) was 29.1% (SD 6.2%) and 25.1% (SD 9.6%), respectively. There was also an increase in sputum eosinophils of 6.2% (P = 0.0004), as well as supernatant eosinophil cationic protein levels. The low‐dose allergen challenge caused an acute fall in FEV1, but had no effect on FEV1 at 24 h after challenge or sputum measurements. Conclusions The high‐dose allergen challenge in asthmatics using ICS induces a late asthmatic response associated with an increase in eosinophilic airway inflammation. This may be a suitable model for studying the effects of novel anti‐inflammatory drugs added to maintenance ICS treatment.